Effect of tungsten dopant on structural and thermochromic properties of vanadium dioxide synthesized by hydrothermal method - Termkoa, Krongtip; Plemjai, Kittiya; Janetanakit, Woraphong; Sirinukunwattana, Krongkran (Bulletin of Applied Sciences, 2022)
The research is to investigate effect of tungsten (W) dopant on thermal and structural properties of synthesized vanadium dioxide (VO2). VO2 was synthesized using vanadium pentoxide (V2O5) as a precursor and oxalic acid (H2C2O4) as a reducing agent with 1:3 molar ratios by hydrothermal method at 260 °C. W with different weight ratios were added to the initial solution to reduce the phase transition temperature and a subsequent thermal annealing. The as-prepared VO2 and W-doped VO2 powder were characterized using differential scanning calorimetry (DSC), X-ray diffraction (XRD), and scanning electron microscope (SEM). DSC results showed that W doping can decrease phase transition temperature depending on concentration of W. The phase transition temperature was decreased to 35 °C when VO2 was doped with the 5 wt. % W.